Thoracoscopic Surgery for Glomus Tumor: An Uncommon Mediastinal Neoplasm and Iatrogenic Tracheal Rupture - Zhongjie Fang; Dehua Ma; Baofu Chen; Huarong Luo (Case Reports in Surgery)
Mediastinal glomus tumors are rarely recognized, and only seven cases have been reported in the literature. Here, we describe a rare mediastinal glomus tumor and review the characteristics of this rare clinical case. The patient was a 50-year-old female who presented with coughing for 3 months. Her chest computed tomography scan demonstrated a localized tumor in the posterior superior mediastinum. Intraoperatively, we found a longitudinal rupture of the membranous trachea above the carina. We completely resected the tumor and repaired the tracheal rupture under a thoracoscopy using a pedicled muscle flap. The tissue was diagnosed as a mediastinal glomus tumor according to its histological and immunophenotypic characteristics.